2008
DOI: 10.1038/nnano.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes introduced into the abdominal cavity of mice show asbestos-like pathogenicity in a pilot study

Abstract: Carbon nanotubes have distinctive characteristics, but their needle-like fibre shape has been compared to asbestos, raising concerns that widespread use of carbon nanotubes may lead to mesothelioma, cancer of the lining of the lungs caused by exposure to asbestos. Here we show that exposing the mesothelial lining of the body cavity of mice, as a surrogate for the mesothelial lining of the chest cavity, to long multiwalled carbon nanotubes results in asbestos-like, length-dependent, pathogenic behaviour. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
1,690
4
34

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 2,349 publications
(1,781 citation statements)
references
References 17 publications
53
1,690
4
34
Order By: Relevance
“…injection of long CNTs, an inflammatory response with granuloma formation and fibrosis occurred, whereas there was a negligible response to short and tangled CNTs. 11 As suggested in studies by Kane et al, 12 we concluded that long fibers are retained in the peritoneal cavity as a consequence of their inability to exit through stomata in the diaphragm, through which short fibers can egress. Herein, we developed a method to deliver CNTs into the more relevant pleural space to expose both the pleural mesothelial layers and assessed the inflammatory responses and the likely mechanism by which length-dependent pathogenicity might occur at this key site.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…injection of long CNTs, an inflammatory response with granuloma formation and fibrosis occurred, whereas there was a negligible response to short and tangled CNTs. 11 As suggested in studies by Kane et al, 12 we concluded that long fibers are retained in the peritoneal cavity as a consequence of their inability to exit through stomata in the diaphragm, through which short fibers can egress. Herein, we developed a method to deliver CNTs into the more relevant pleural space to expose both the pleural mesothelial layers and assessed the inflammatory responses and the likely mechanism by which length-dependent pathogenicity might occur at this key site.…”
supporting
confidence: 55%
“…Short CNTs did not elicit a significant inflammatory reaction at any point examined and, indeed, the results obtained from short CNT-treated mice mirrored those of the vehicle controls. These results suggest that, like asbestos, the toxicity of CNTs for the pleura adheres to the fiber pathogenicity paradigm 11 regarding the role of length in this model of direct pleural exposure.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous studies indicated that longer fibers could not be fully phagocytosed by macrophages, and induced cytotoxicity [>15 ÎŒ m in length (Searl et al ., 1999; Poland et al ., 2008)]. However, the MWCNTs used in the present study were much shorter (average length = 2.4 ÎŒ m; 96%, < 0.5–10 ÎŒ m 96%; 2.8%, 10–15 ÎŒ m; 1.1%, > 15 ÎŒ m) than those shown to block phagocytosis.…”
Section: Discussionmentioning
confidence: 56%